Exploring two distinct gentamicin prescribing protocols in UK hospitals: a mixed-methods realist evaluation. Issue 12 (23rd December 2021) - Dyar, Nadine; Mattick, Karen; Bethune, Rob
Abstract : Objectives: Gentamicin is the aminoglycoside antibiotic of choice in the UK. It has a narrow therapeutic index: underdosing results in inefficacy while overdosing is characterised by nephrotoxicity and ototoxicity. To improve patient safety, hospitals have protocols for the prescription of gentamicin, which vary in complexity and approach. This study aimed to explore two distinct protocols for prescribing gentamicin in hospital settings, in order to understand the mechanisms they trigger and the outcomes they achieve. Setting: A mixed-methods realist evaluation explored gentamicin prescribing protocols in two hospital surgical admissions units in South West England between January and August 2018. Site 1 had a traditional, complex protocol, while site 2 took a simplified protocol. Participants: Testing the initial programme theory (IPT) involved semi-structured audio-recorded interviews of a volunteer sample of healthcare professionals (HCPs) involved in the prescribing and administering process, alongside a clinical audit reviewing accuracy of gentamicin prescribing. Outcome measures: Three sequential phases were used to identify factors in a successful protocol: IPT generation; testing; refinement of the IPT. The IPT was generated by literature search and analysis of existing protocols of sites 1 and 2. Refinement of the IPT synthesised the results of the quantitative and qualitative research to identify the key characteristics of a successful protocol. Results: One hundred gentamicin prescriptions were reviewed, with a mean accuracy of gentamicin prescribing at site 1 of 65.67% and at site 2 of 78.79% (p<0.01). Thirty HCPs were interviewed. Key contexts were identified including prescriptiveness, experience and availability of patient information. These triggered hidden mechanisms including uncertainty, fear, confidence and frustration leading to both intended outcomes but also unintended outcomes such as deviation from protocol and unnecessary gentamicin levels. Conclusions: A simplified prescribing protocol for gentamicin is better accepted by prescribers, leading to better adherence to protocol and more accurate prescribing.